2021
DOI: 10.1186/s12951-021-01173-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal regulation of angiogenesis/osteogenesis emulating natural bone healing cascade for vascularized bone formation

Abstract: Engineering approaches for growth factor delivery have been considerably advanced for tissue regeneration, yet most of them fail to provide a complex combination of signals emulating a natural healing cascade, which substantially limits their clinical successes. Herein, we aimed to emulate the natural bone healing cascades by coupling the processes of angiogenesis and osteogenesis with a hybrid dual growth factor delivery system to achieve vascularized bone formation. Basic fibroblast growth factor (bFGF) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…Various studies have shown that the dual release of growth factors at different kinetic rates leads to successful bone tissue repair [ 80 , 81 ]. To release bFGF and BMP-2 in a spatiotemporal manner, Zhou et al designed a composite hydrogel including GelMA-bFGF and mineral and microparticles (MCM)-BMP-2 ( Figure 3 B) [ 82 ]. When bFGF molecules were rapidly released and BMP-2 released over time from composite gels, a significantly enhanced vascularized bone regeneration was observed compared to the single release system.…”
Section: Applications Of Gelma With a Focus On Musculoskeletal Regene...mentioning
confidence: 99%
“…Various studies have shown that the dual release of growth factors at different kinetic rates leads to successful bone tissue repair [ 80 , 81 ]. To release bFGF and BMP-2 in a spatiotemporal manner, Zhou et al designed a composite hydrogel including GelMA-bFGF and mineral and microparticles (MCM)-BMP-2 ( Figure 3 B) [ 82 ]. When bFGF molecules were rapidly released and BMP-2 released over time from composite gels, a significantly enhanced vascularized bone regeneration was observed compared to the single release system.…”
Section: Applications Of Gelma With a Focus On Musculoskeletal Regene...mentioning
confidence: 99%
“…10), which was largely accredited to the FGF-induced bone vascularization. 92 In the case of bone damage, after the damage has occurred, immune cells (including macrophages, neutrophils, and T lymphocytes) are employed and contribute to immunomodulation and bone dynamics regulation at the site of injury. Therefore, the manipulation of immune cells is an encouraging strategy to produce a favorable osteo-immune environment for bone regeneration.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…10 Schematic illustration of (A) the fabrication and (B) the application of the F-G/B-M hybrid hydrogel. 92…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Studies have shown that FGF-2 in gelatin hydrogels can be released consistently at relatively low concentrations ( Nguyen et al, 2015 ). FGF-2 delivered via gelatin hydrogels has therapeutic potential in ischemic limb and heart injury and bone formation for fracture repair ( Nakajima et al, 2004 ; Zhou et al, 2021 ). Therefore, FGF-2 encapsulated within gelatin hydrogels offers a promising strategy for the treatment of ONFH.…”
Section: Therapeutic Applications Of Growth Factors For Osteonecrosis...mentioning
confidence: 99%